Ixtisoslashtirilgan ta’lim jarayonida kognitiv yondashuvning o‘quvchilardagi iqtidorni rivojlantirish xususiyatlari - Pazilov, M.A (SCIENCE and SOCIETY, 2025)
This article discusses the features and significance of the cognitive approach in the development of stu- dents' talents in the process of specialized education.
Keywords: cognitive education; cognitive approach; specialized education; giftedness; talent; teacher; paradigm; context